Dinamika Politik Lokal dan Strategi Partai: Peran PKS dalam Kontestasi Pemilu di Kota Padangsidimpuan - Efendi, Erwin (PT Anugerah Literasi Indomedia, 2025)
This study is motivated by the dynamics of local politics in Padangsidimpuan City, where Islamic-based parties have increasingly shaped electoral processes, particularly the role of the Prosperous Justice Party (PKS). Although PKS is widely recognized as an ideological party, its involvement in the mayoral election demonstrates a pragmatic approach to coalition-building. This research aims to analyze PKS’s coalition strategy with Gerindra, PKB, and PBB in supporting the candidacy of Letnan Dalimunthe and Harry Pahlevi Harahap, and to examine how this coalition strengthens PKS’s political position within the local electoral contest. The study employs a qualitative approach with a case study design, involving in-depth interviews with party elites, analysis of campaign documents, and observation of coalition activities. Data were analyzed through reduction, categorization, and conclusion drawing based on empirical findings. The results indicate that PKS plays a strategic role as a key actor in mobilizing voter support and consolidating its electoral base. The coalition with Gerindra, PKB, and PBB was formed based on shared political visions and electoral calculations, which empirically expanded the support network for the endorsed candidates. Beyond serving as a supporting party, PKS successfully integrated its political agenda into the joint campaign platform, enhancing coalition legitimacy and strengthening the candidates’ position in the election. The study implies that political coalitions function as an essential instrument for reinforcing local democracy through inter-party synergy and increasing public political participation. The novelty of this research lies in its analysis of PKS’s dual role as both an ideological and pragmatic actor in constructing electoral coalitions at the municipal level. Penelitian ini dilatarbelakangi oleh dinamika politik lokal Kota Padangsidimpuan yang menunjukkan meningkatnya peran partai berbasis Islam dalam proses elektoral, khususnya Partai Keadilan Sejahtera (PKS). Meskipun PKS dikenal sebagai partai ideologis, keterlibatannya dalam pemilihan wali kota dan wakil wali kota menunjukkan praktik politik koalisi yang semakin pragmatis. Penelitian ini bertujuan untuk menganalisis strategi koalisi PKS dengan Gerindra, PKB, dan PBB dalam mendukung pasangan Letnan Dalimunthe dan Harry Pahlevi Harahap serta memahami bagaimana koalisi tersebut berkontribusi pada penguatan posisi PKS dalam kontestasi politik lokal. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus, melibatkan wawancara mendalam dengan pengurus partai, analisis dokumen kampanye, serta observasi aktivitas politik koalisi. Data dianalisis melalui teknik reduksi, kategorisasi, dan penarikan kesimpulan berbasis temuan empiris. Hasil penelitian menunjukkan bahwa PKS memainkan peran strategis sebagai penggerak utama dalam mobilisasi dukungan dan konsolidasi basis pemilih. Koalisi dengan Gerindra, PKB, dan PBB terbentuk atas dasar kesesuaian visi politik dan kalkulasi elektoral, yang secara empiris terbukti memperluas jangkauan dukungan calon yang diusung. Selain bertindak sebagai partai pendukung, PKS berhasil mengintegrasikan agenda politiknya dalam program kampanye bersama, meningkatkan legitimasi koalisi serta memperkuat posisi kandidat dalam pemilu. Implikasi penelitian ini menegaskan bahwa koalisi politik menjadi instrumen penting dalam memperkuat demokrasi lokal melalui sinergi antarpartai dan peningkatan partisipasi politik masyarakat. Kebaruan penelitian terletak pada analisis peran PKS sebagai aktor politik yang menggabungkan orientasi ideologis dengan strategi pragmatis dalam membentuk koalisi elektoral di tingkat kota.